Project on Human Development in Chicago Neighborhoods (PHDCN): Primary Female Caregiver, Wave 3, 2000-2002 - Earls, Felton J. ([Verlag nicht ermittelbar], 2007)
The Project on Human Development in Chicago Neighborhoods (PHDCN) was a large-scale, interdisciplinary study of how families, schools, and neighborhoods affect child and adolescent development. One component of the PHDCN was the Longitudinal Cohort Study, which was a series of coordinated longitudinal studies that followed over 6,000 randomly selected children, adolescents, and young adults, and their primary caregivers over time to examine the changing circumstances of their lives, as well as the personal characteristics, that might lead them toward or away from a variety of antisocial behaviors. Numerous measures were administered to respondents to gauge various aspects of human development, including individual differences, as well as family, peer, and school influences. One such measure was the Primary Female Caregiver instrument. It was administered to the subjects' primary female caregiver in Cohorts 0, 3, 6, 9, and 12 and to subjects in Cohorts 15 and 18. It obtained information related to the female most responsible for raising the subject. It is complemented by PROJECT ON HUMAN DEVELOPMENT IN CHICAGO NEIGHBORHOODS (PHDCN): PRIMARY MALE CAREGIVER, WAVE 3, 2000-2002 (ICPSR 13731).